2023
DOI: 10.1002/chem.202203774
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Combinations of B(C6F5)3 and N2‐Derived Molybdenum Nitrido Complexes for Heterolytic Bond Activation

Abstract: Two different dinitrogen-derived molybdenum nitrido complexes varying by their geometry, ligand spheres and oxidations states were shown to engage their N ligand in dative bonding with the strong Lewis acid B(C 6 F 5 ) 3 . The stable adducts were assessed for frustrated Lewis pair-type heterolytic EÀ H bond splitting of hydrosilanes (E = Si) and HB(C 6 F 5 ) 2 .Whereas SiÀ H bond activation was achieved, HB(C 6 F 5 ) 2 was shown to substitute B(C 6 F 5 ) 3 in a quantitative or equilibrated fashion, depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“… [29] We have also demonstrated that weakly polar substrates E−H (E=R 3 Si, PinB) react readily with the N 2 derived [(PPP)Mo(N)I] complex to form the corresponding imido‐hydride complex [30–32] . Alternatively, in the presence of a strong Lewis acid, heterolytic addition of Et 3 Si−H was observed [33] . Following a bio‐inspired approach, i.e.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“… [29] We have also demonstrated that weakly polar substrates E−H (E=R 3 Si, PinB) react readily with the N 2 derived [(PPP)Mo(N)I] complex to form the corresponding imido‐hydride complex [30–32] . Alternatively, in the presence of a strong Lewis acid, heterolytic addition of Et 3 Si−H was observed [33] . Following a bio‐inspired approach, i.e.…”
Section: Introductionmentioning
confidence: 94%
“…[30][31][32] Alternatively, in the presence of a strong Lewis acid, heterolytic addition of Et 3 SiÀ H was observed. [33] Following a bio-inspired approach, i.e. using H + /e À sources, catalysts based on transition metal complexes have been reported first in 2003 opening the way to impressive developments.…”
Section: Introductionmentioning
confidence: 99%
“…Other Mo-pincer complexes have also been found to effectively catalyze ammonia formation or, in some cases, to effect the key N2 cleavage step though not as part of an catalytic cycle for ammonia formation. 12,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Figure 1. (a) Schrock's (triamidoamine)Mo catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…12 f ,19 Besides, the NN→LA linkage may show FLP-type reactivity, such as Si–H bond heterolytic splitting, resulting in N 2 silylation. 12 g ,20 Of note, the analogous reaction employing H 2 for N–H bond formation 21 is yet to be achieved and is challenged by the propensity of H 2 to easily substitute N 2 . 22 Alternatively, [R 3 XH] + [R′ 3 BH] – (X = N or P) ion pairs delivered by FLP H 2 splitting 23 have been employed to protonate N 2 .…”
Section: Introductionmentioning
confidence: 99%